Disaster risk management in agriculture : case studies in South Asian countries. - Ha, Huong; Fernando, R. Lalitha S.; Mahajan, Sanjeev Kumar (Momentum Press Engineering, 2019)
The challenges related to disaster risk management (DRM) in the agricultural sector are now widely linked to sustainable environment. The fact remains that almost every day a disaster strikes in some part of the world. The regular occurrence of natural and man-made disasters has forced the worldwide communities to look for novel solutions to prevent and mitigate such disasters. This volume brings together probing studies to disseminate the work of outstanding scholars and practitioners, especially in South Asian countries. Thus, it highlights the need to amalgamate and coordinate the resources and agencies involved in DRM in agriculture to ensure the quality of life to the victims after disasters. The authors incorporate specific themes correlated with DRM in South Asia. They intend to assess: (i) the consequences of distinct disaster risks in agriculture, (ii) the ways in which diverse disaster risk problems are handled in distinct settings, and (iii) the different methodologies embraced by different sectors to prepare for disaster risk.